Literatura infantil brasileira e estudos literários - Marisa Lajolo (Estudos de Literatura Brasileira Contemporânea)
The article discusses some features undertaken by production and circulation of contemporary Brazilian works aimed at children and adolescents, with base on the changes that affected Brazilian society for the last 40 years, mainly regarding financial investments and legitimization of cultural property.